2015
DOI: 10.1586/14779072.2016.1117388
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative management of heart failure in pediatric patients

Abstract: Low cardiac output syndrome (LCOS) is a well-described entity occurring in 25-65% of pediatric patients undergoing open-heart surgery. With judicious intensive care management of LCOS, most patients have an uncomplicated postoperative course, and within 24 h after cardiopulmonary bypass, the cardiac function returns back to baseline. Some patients have severe forms of LCOS not responsive to medical management alone, requiring temporary mechanical circulatory support to prevent end-organ injury and to decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 135 publications
0
11
1
Order By: Relevance
“…It has also been suggested that neutrophil interactions with other myocardial inflammatory cells after acute MI may result in myocardial dysfunction [21]. Although the mechanism of myocardial damage is different in our study population, there are known deleterious effects on the myocardium resulting from cardiac operation and CPB, which contribute to postoperative low cardiac output syndrome [23]. It is feasible that the negative sequelae attributed to neutrophil migration in adult patients after MI could be extrapolated to our study population and that patients with a higher neutrophil count preoperatively may thus be at increased risk of adverse outcomes.…”
Section: Neutrophiliamentioning
confidence: 74%
“…It has also been suggested that neutrophil interactions with other myocardial inflammatory cells after acute MI may result in myocardial dysfunction [21]. Although the mechanism of myocardial damage is different in our study population, there are known deleterious effects on the myocardium resulting from cardiac operation and CPB, which contribute to postoperative low cardiac output syndrome [23]. It is feasible that the negative sequelae attributed to neutrophil migration in adult patients after MI could be extrapolated to our study population and that patients with a higher neutrophil count preoperatively may thus be at increased risk of adverse outcomes.…”
Section: Neutrophiliamentioning
confidence: 74%
“…Low cardiac output syndrome (LCOS) is the most common complication following cardiac surgeries. The incidence of LCOS in the surgical treatment of congenital heart disease (CHD) has been reported to be 25-60% [1], associated with a significant risk of mortality among patients [2,3]. LCOS is associated with a decreased ejection fraction and decreased oxygen supply, which may cause hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, for patients undergoing the Fontan procedure, transpulmonary gradient and chest tube drainage were significantly lower in the vasopressin group compared to placebo [47] . Norepinephrine has been used for patients with LCOS and low systemic vascular resistance, but less commonly than epinephrine and vasopressin [48] . Finally, in a recent review of the PHIS database by Loomba and Flores [15] , while the use of catecholaminergic inotropes and vasopressors after cardiac surgery have decreased over the past ten years, the use of vasopressin has increased.…”
Section: Vasopressin and Norepinephrinementioning
confidence: 99%